Intuitionistic fuzzy kernel matching pursuit ensemble based target recognition - Xiao-dong YU; Ying-jie LEI; Ya-fei SONG; Shao-hua YUE; Jun-hong HU (Tongxin xuebao)
Considering that the generalization of the learning machine performed poorly in the present intuitionistic fuzzy kernel matching pursuit algorithm(IFKMP)due to its training method and stopping criteria,a new recognition method based on intuitionistic fuzzy kernel matching pursuit ensemble(IFKMPE)was proposed by introducing the idea of ensemble learning.In IFKMPE,the double perturbation strategy including sample and parameter perturbation was applied to generate the sub-learning machine,the recognition results were fused by the principle of majority voting,and therefore both the classify accuracy and generation ability were enhanced.Simulation results show the new algorithm IFKMPE performs better in terms of recognition accuracy and stability of sample learning compared with the traditional ones.